Memória e narrativas surdas: o que sinalizam as professoras sobre sua formação? - Silva, Bianca Gonçalves da (2012)
This Master s degree dissertation intends to contribute to the debate around deaf people education, based on the process of deaf teachers formation, taking into account their formation history. The research aims to understand the constitution of the deaf teachers identity, more specifically, to analyze, through the narratives, the constituent processes experienced throughout their lives which have enabled the construction of a teaching identity. The data collected in this research was searched through the contribution of three deaf teachers, using autobiographical narratives of their life and teaching formation history. Thus, this research was created and analyzed dialoging with authors who deepen in the deaf related studies, involving the Deaf Studies and their dialogues with the Cultural Studies, also, authors who work with the (auto) biographical method and formation, tying to life narratives. In the data collection, it was developed a strategic methodology aiming to achieve the main goals of the research. Three semi-structured group meetings were organized, recorded and in Brazilian Sign Language. With the teachers reports about their life histories some themes could be highlited: oralism, the visual experience as a deaf cultural marker, literacy, child literature, deaf literature, among other issues that were shown in the narratives. When analyzed, they pointed to a possible constitution of teaching identities based on their experiences. It was also possible to find that, as culture is produced, so is identity, in other words, from the teachers reports, which showed their experiences, emphasized such issues, showed a commitment to teaching according to their deaf students needs, creating a pedagogy of the deaf.